Building a Smart Village Based on Entrepreneurship in Karangrejo Hamlet, Ngringo Village, Jaten District, Karanganyar Regency: Membangun Desa Cerdas Berbasis Kewirausahaan di Dusun Karangrejo Desa Ngringo Kecamatan Jaten Kabupaten Karanganyar - Ramadhian Agus Triono Sudalyo; Nurita Elfani Prasetyaningrum (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2024)
The development of entrepreneurship-based Smart village in Karangrejo Hamlet, Ngringo Village, Jaten District, Karanganyar Regency has been the focus of efforts to improve the economy and the well-being of the community. One tangible step in supporting this is through training conducted on January 22, 2024. This training was held in two sessions, the first focusing on Digital Marketing for MSMEs, while the second session focused on Email Marketing in the Accounting Context. The training was attended by 24 MSME actors from various sectors, including culinary, crafts, and services. The first session was led by Ramadhian Agus Triono Sudalyo, S.Ag., S.Kom., M.M from the Informatics Engineering Study Program at the Surakarta University, while the second session was delivered by Nurita Elfani Prasetyaningrum, S.E., M.Si from the Accounting Study Program at the Surakarta University. The aim of this training is to provide MSME participants with new knowledge and new skills to use digital technology to increase the efficiency and effectiveness ofÂ businesses in the village of Karangrejo.. Thus, it is expected to create an inclusive and highly competitive environment in Karangrejo Hamlet, which will ultimately contribute to the sustainable development of the Smart village.